Work team effectiveness: importance of organizational culture, work climate, leadership, creative synergy, and emotional intelligence in university employees - Geraldo-Campos, Luis Alberto (2024)
[Background]: In university contexts, the effectiveness of work teams is vital for institutional success and the personal development of an institution’s members. Objective: Our aim is to understand the relationships between emotional intelligence, team leadership, organizational culture, work climate, and creative synergy with team effectiveness. [Methods]: We used a cross-sectional predictive design study using structural equation modeling (SEM), in which 512 surveys of employees of a private Peruvian university were analyzed. [Results]: Leadership and emotional intelligence were found to significantly improve team effectiveness. In addition, organizational culture, work climate, and creative synergy act as mediators in these relationships, enhancing team effectiveness. The adjusted model presented adequate incremental x 2 = 9452.498, gl = 3391, p < 0.001 and comparative (TLI = 0.998, CFI = 0.998, RMSEA = 0.017 y SRMR = 0.033) goodness-of-fit indices. [Conclusions]: The results showed that the development of emotional competencies and leadership skills is essential to optimize the effectiveness of work teams in universities. This integrated model not only provides a solid theoretical framework for future research, but also offers practical recommendations for improving the management and performance of work teams.